Development of a procedure to accurately measure the low-temperature operating limits of elastomeric seals. Issue 9 (September 2016) - Douglas, Andrew; Devlen, Ozan; Mitchell, Matthew; Edwin-Scott, David; Neal, Mark
Abstract : The research described in this article aims to show that it is possible to develop a testing method that gives a closer link to a "real-world" low-temperature sealing capability than is achievable through existing laboratory tests. This will result, for the first time, in an industry agreed specification that all reputable seal suppliers will be able to use to give end-users reliable guidance on the low-temperature operating limits of their compounds.